Filipinx : heritage recipes from the diaspora - Dimayuga, Angela; Mishan, Ligaya (Abrams, 2021)
"In her debut cookbook, acclaimed chef Angela Dimayuga shares her passion for Filipino food with home cooks. Filipinx offers 100 deeply personal recipes--many of them dishes that define home for Angela Dimayuga and the more than four million people of Filipino descent in the United States"--